IMPROVING LECTURERS' COMPETENCIES IN THE APPLICATION OF QUANTITATIVE RESEARCH METHODOLOGY AND QUALITATIVE FOR THE STRENGTHENING OF SCIENTIFIC PUBLICATIONS - Sugiyono; Nolla Puspita D.; Agelina E. Rumengan; Ely Kurniawati (RADJA PUBLIKA, 2025)
This community service program aims to improve lecturers' skills in implementing both quantitative and qualitative research methods to support increased scientific publications. Challenges faced include a lack of understanding of research design, limitations in data analysis capabilities using software, and low productivity in scientific publications. The method used in the implementation involves a training and guidance approach consisting of needs analysis stages, learning research methodology, scientific article writing training, intensive guidance, and checking through pre-tests and post-tests. The impact of this activity shows an increase in lecturers' skills in understanding research methodology, data analysis skills, and scientific article writing skills that meet the standards of reputable journals. In addition, this activity also plays a role in increasing lecturers' motivation and confidence in conducting scientific publications. Thus, this program contributes to creating an academic culture based on research and publications and increasing the quality and quantity of lecturers' scientific publications in a sustainable manner